The effects of corporate governance practices on firm-level financial performance: evidence from Borsa Istanbul Xkury companies - Saygili, Arikan Tarik; Saygili, Ebru; Taran, Alina (Journal of Business Economics and Management, 2021)
Corporate governance (CG) is a fundamental criteria for enhancing investors’ and stakeholders’ trust, relatively recently recognized in emerging markets. This study investigates the effects of CG practices on the firm-level financial performance of Borsa Istanbul XKURY-indexed companies during 2007–2019. Four specific aspects of CG are analysed: shareholders’ rights, public disclosure and transparency, stakeholders’ rights, and board of directors functioning, as defined by the Turkish Code of Corporate Governance, in line with international principles of CG issued by OECD. Alternative estimations of panel regression analysis indicate a positive association between stakeholder-oriented governance practices and firm-level financial performance expressed by accounting measures for both financial and non-financial companies. Shareholder protection policies have a negative influence on accounting-based performance, especially for non-financial industries, whereas the corporate practices related to board of directors and public disclosure vary between financial and non-financial entities. These findings contribute to international research on CG implications for emerging markets, providing evidence about the importance of stakeholders’ protection and the distinctive effects of CG dimensions for corporate financial performance.